Trades access common core. Line E, Electrical fundamentals, Competency E-2, Identify common circuit components and their symbols /|cRod Lidstone (Camosun College), lead writer. - Lidstone, Rod; Camosun College; British Columbia. Ministry of Technolgy, Innovation and Citizens' Services; BC Open Textbook Project; BCcampus (Ministry of Technology, Innovation and Citizens' Services, 2015)
"Many types of electric devices are used in almost every trade. Mechanical trades will find electrical devices in every motor-driven vehicle. Construction trades will encounter them in most construction projects. To be able to recognize or troubleshoot electrical devices, you must be familiar with the correct terminology and symbols used to identify them"--BC Campus website.
This work is licensed under the Creative Commons Attribution-NonCommercial-ShareAlike License.
"Copyright Camosun College"--P. 2.
This bibliographic record is available under the Creative Commons CC0 "No Rights Reserved" license.
Description based on online resource; title from pdf title page (viewed on January 7, 2016).
Keywords: Electric circuits -- Textbooks; Electronic books